ANALYSIS OF "MIXUE" COMMUNICATION NETWORK AS ELECTRONIC WORD OF MOUTH (E-WOM) USING SOCIAL NETWORK ANALYSIS - Melati Andriani; Rizky Wulan Ramadhani; Sabrina Rahma Utami (Journal of Digital Media Communication, 2023)
Netizens upload the keyword "Mixue" on Twitter, which can become an electronic word of mouth (E-WoM). E-WoM is one of the dominant factors influencing purchase demand for a product. Using the keyword "Mixue" to become a trending topic creates a communication network to disseminate information related or not to Mixue. This study aimed to determine the distribution of the "Mixue" network as a medium for electronic word of mouth using Social Network Analysis (SNA). The theory used is computer-mediated communication. The research method is quantitative with the SNA approach. Researchers crawled data on 10,000 tweets on December 27, 2022, when the keyword "Mixue" became a trending topic. The researcher used the application. The results showed that the "Mixue" communication network involved 7,702 actors and 8,391 conversations. @handokotjung became an important actor after posting a humorous tweet about Mixue's expansion in Indonesia. The tweet achieved 3.3 million views, 2,277 replies, 13.6K retweets, 2,682 excerpts retweeted, and 67.5K likes. The other actors also got into the conversation regarding Mixue. The perpetrators communicate with each other by replying, retweeting, retweeting quotes, or uploading their tweets, which can be electronic word-of-mouth (E-WoM) media accessed by anyone without exception. Mixue can use social media and impoertant actors to increase people's buying interest in Mixue